Risk Factors for Acute Pesticide Poisoning in Developing Countries: A Systematic Review - Marcus, Hannah; De Souza, Russell J (Global Health: Annual Review, 2020)
Acute pesticide poisoning (APP) is a major public health issue in developing countries. While much country-specific research has been conducted on APP, international epidemiological trends have been difficult to describe. In this systematic review, we summarize individual-level findings from multiple countries. Prominent risk factors identified for both voluntary and involuntary cases include young age, lack of farming experience, low socioeconomic status, lack of education, risky pesticide handling and storage practices, insufficient knowledge of pesticide hazards, and high organophosphate use. In combination with region-specific findings available in the literature, this review contributes to the global understanding of APP as needed for corresponding policy action.